Vascularization of skin following implantation of an arteriovenous pedicle - Falco, Nancy A. (1992)
In a rat model, a skin flap was fabricated by implantation of a distally ligated arteriovenous pedicle. The femoral artery and vein were implanted as a unit beneath the abdominal skin, a portion of which was later raised as an island flap, based on these vessels. Percentage area of survival, tissue blood flow, and pattern of vascularity were compared in two groups of flaps. In group I, the pedicle to be implanted was dissected with a cuff of surrounding muscle still attached; in group II, the pedicle was skeletonized to the level of adventitia. Flap survival in the two groups was similar (73% vs.77%), as was skin blood flow (5.4 vs. 5.7 ml/100 g/min). Angiography demonstrated two principal patterns of vascularization: connection between donor and recipient vessels (inosculation), and sprouting and arborization of new vessels. Strengths and limitations of this and other models of flap “prefabrication” are discusssed.